Le “monstrueux” pédagogique. Qui ? Quoi ? Comment ? Pourquoi ? - Choppin de Janvry, Thibaud (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
This article aims at studying the historical dynamics of knowledge, as understood by G. Bachelard. It more precisely focuses on the teacher-student dialectic and its interrationalism by asking the apparently trivial questions: “Who?”, “What?”, “How?” and “Why?”. We first grasp anchored and rectifying subjects, who never cease to undulate. We secondly surprise scientific thought in its “permanent state of pedagogy”, merged in a multi-layered reality that can only be detected by deformation. Finally, this article proposes to see the pedagogical instant through the morphological gap around which it builds, in-between animus and anima. The term “monstrous” is therefore used to express the androgynous project of pedagogy, and to sign the non-place of a second time – an ambiguous time of knowledge, and dreams.